Alternative Forms of Resilience. A typology of approaches for the study of Citizen Collective Responses in Hard Economic Times - Kousis, Maria; Paschou, Maria (PARTECIPAZIONE E CONFLITTO, 2017)
A variety of theoretical and conceptual perspectives have been applied to studying collective citizen initiatives arising in response to hard economic times, such as solidarity-based exchanges and networks, cooperative structures, barter clubs, credit unions, ethical banks, time banks, alternative social currency, citizens' self-help groups, neighbourhood assemblies and social enterprises. Since the global financial crisis of 2008, scholarly attention on novel, alternative, resilient structures has increased, especially in regions that have been most affected. A comprehensive literature review is therefore needed on these initiatives which usually aim to meet basic needs such as food, shelter, health and education at the community level, or build and envision autonomous communities. This paper has four aims. First, it proposes a new, all-encompassing conceptual framework, alternative forms of resilience, to embrace all issues and groups related to such initiatives, during the new millennium and its economic and political challenges, while taking into account the impact of the 2008 crisis. Secondly, it offers a comprehensive literature review on collective citizen initiatives studied through different theoretical, methodological and conceptual understandings. Thirdly, it provides a new typology of several approaches on novel, collective and solidarity-oriented critical resilience initiatives which take into account political issues, be they policy or social-movement related. Finally, it points to future research areas which would aim to systematically address the political and non-political features of citizen-collective responses.